The Political Economy of Entrepreneurship - Robin Douhan; Magnus Henrekson (Research Institute of Industrial Economics (IFN), 2007)
We outline a politico-economic growth system centered around the entrepreneur. By defining entrepreneurs in relation to economic rents we are able to develop a more general theory comprising central aspects of research within the fields of entrepreneurship/small business, public choice and new institutional economics. The entrepreneurial function is shown to depend crucially on the existing institutional framework. We also point to the necessity of viewing institutions as endogenously influenced by entrepreneurs. A typology of entrepreneurship is developed to further our understanding of the bilateral effects between institutional context and entrepreneurial activity. We use developments in modern history as a real-world context to substantiate our framework. Particular attention is devoted to the effects of enforcement of property rights and taxation, two of the most prominent institutions in the literature.
Keywords: H32; L25; L50; M13; O31; P14; 330; Entrepreneurship; Industrial Policy; Innovation; Property Rights; Regulation; Self-employment; Tax Policy; Wirtschaftstheorie; Entrepreneurship-Ansatz; Institutionelle Infrastruktur; Politisches System; Innovation; Theorie